Transformation of the Green Accounting 4.0 Era towards Society 5.0: A Literature Study - Putra, Reza Eka; Sayekti, Yosefa; Arif, Alfi (Research Horizon, 2024)
While the study of the use of smart robots in production known as the Industrial Revolution 4.0 continues rapidly and competition in the right proportion with this and businesses that do not want to be left behind must follow suit. The purpose of this study is to review the transformation of green accounting from Industry 4.0 to Society 5.0. Misinformation from one of the business departments will affect the entire system, especially in the accounting department that records the financial movements of the business and reports the results effectively in making decisions that affect the entire business based on these results. The use of intelligent systems helps reduce human errors and the system acts faster while the system used in traditional accounting is abandoned. The study was conducted through a literature review of several journals so that the practice of green accounting towards changes to the era of society 5.0 can be known. The expected results of this literature review are that with the transformation will make the accounting and auditing professions work smartly using updated technology, the need for brain power to analyze system output will increase. In this context, especially those who practice the accounting profession must always renew themselves. The contribution of this study is to develop the concept of green accounting which is still often overlooked in Indonesia.